2017
DOI: 10.3847/1538-4357/aa8a64
|View full text |Cite
|
Sign up to set email alerts
|

On the Magnetic Squashing Factor and the Lie Transport of Tangents

Abstract: The squashing factor (or squashing degree) of a vector field is a quantitative measure of the deformation of the field line mapping between two surfaces. In the context of solar magnetic fields, it is often used to identify gradients in the mapping of elementary magnetic flux tubes between various flux domains. Regions where these gradients in the mapping are large are referred to as quasi-separatrix layers (QSLs), and are a continuous extension of separators and separatrix surfaces. These QSLs are observed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…In order to analyze our simulation results, we extracted representative snapshots of the magnetic field for the SN and TN configurations, which are indicated with numeric subscripts (e.g., SN 3 ) for the times listed in Table 2. We then applied the QSLsquasher tool developed by Tassev & Savcheva (2017; see also Scott et al 2017) to create surface and volume renderings of the slog 10 Q ⊥ . We also calculated the locations of the null points in each snapshot using a routine developed by F. Chiti at the University of Dundee and based on the method of Haynes & Parnell (2007).…”
Section: Simulation Design and Methodsmentioning
confidence: 99%
“…In order to analyze our simulation results, we extracted representative snapshots of the magnetic field for the SN and TN configurations, which are indicated with numeric subscripts (e.g., SN 3 ) for the times listed in Table 2. We then applied the QSLsquasher tool developed by Tassev & Savcheva (2017; see also Scott et al 2017) to create surface and volume renderings of the slog 10 Q ⊥ . We also calculated the locations of the null points in each snapshot using a routine developed by F. Chiti at the University of Dundee and based on the method of Haynes & Parnell (2007).…”
Section: Simulation Design and Methodsmentioning
confidence: 99%
“…It is found that the sigmoidal field has a highest twist of 0.8, corresponding to the erupting threads that distribute in both northern and southern parts of the minisigmiod. We calculate the squashing factor Q, which measures the change of magnetic field connectivity (Demoulin et al 1996;Titov et al 2002;Titov 2007), following the method of Tassev & Savcheva (2017) and Scott et al (2017). Similar to what is revealed in observed EUV images, the distribution of the Q value also presents two groups of sigmoidal structures.…”
Section: Twist Squashing Factor and Electric Currentmentioning
confidence: 79%
“…Equation 22 with initial condition 23 , generalizes the field-line deviation to include affine transformations in the connectivity parameter representations (see, e.g. , Tassev and Sevcheva, 2017 ; Scott, Pontin, and Hornig, 2017 , for application).…”
Section: The Integral Curve Description Of Vector Field Geometrymentioning
confidence: 99%
“…The QSL is often described in terms of the “squashing” of a flux tube (see, e.g. , Titov, 2007 ; Tassev and Sevcheva, 2017 ; Scott, Pontin, and Hornig, 2017 ); essentially, a relational measure between the eccentricity of the flux-tube cross-sectional area at the system boundaries, and hence is inherently 2D. Moreover, the squashing of a flux tube is defined entirely independent of rotation.…”
Section: Geometric Deformation Of a Congruencementioning
confidence: 99%
See 1 more Smart Citation